KONSEP HUKUM PEMBUKTIAN PROSTITUSI MELALUI MEDIA SOSIAL DALAM ASPEK HUKUM PIDANA - Ayu Dian Ningtias; Suisno Suisno (Prodi Ilmu Hukum, Universitas Teuku Umar, 2021)
Sex workers through social media are now a criminal problem that is often found through social media, Instagram, WhatsApp, Facebook, etc. How is the evidence in the aspect of criminal law in cyber crime in the form of commercial sex workers through social media, is the focus of this research. The type of legal research carried out is juridical normative, so the approach used is the statute approach and the conceptual approach. Proof of cyber prostitution is the same as in Article 184 of the Criminal Procedure Code, namely regarding evidence in the form of witness statements, expert statements, letters, instructions. However, in an ITE act , case that becomes evidence, it can be said to be digital evidence because it is in the form of Electronic Information and / or Electronic Documents in accordance with the criteria in Article 1 number 1 and number 4 of Law No. 19 of 2016 so that this digital evidence can clarify the facts that have occurred supported by other evidence.